Effect of Various Orthodontic Adhesives on Shear Bond Strength After Thermal Cycling. (Bangladesh Journal of Medical Science, 2025)
Background Orthodontic treatment involves the use of adhesives to bond brackets to enamel surfaces. The treatment’s efficacy depends on how long these bonds last. Orthodontic adhesives’ shear bond strength (SBS) could be affected by thermal cycling, which mimics the conditions in the mouth. The purpose of this research was to compare the SBS of different orthodontic adhesives following thermal cycling. Materials and Methods For this study, we randomly assigned 40 removed premolars from adults to one of four groups: Group A (resin- modified glass ionomer cement), Group B (light-cured composite resin), Group C (self-etch adhesive), or Group D (cyanoacrylatebased adhesive). Each group consisted of ten teeth. Over the course of 1,000 cycles, the samples were heated to temperatures ranging from 5 to 55 degrees Celsius. Using a universal testing equipment at a crosshead speed of 1 mm/min, SBS testing was conducted. Adhesive remnant index (ARI) scoring was applied to the debonded surfaces. Results In MPa, the average SBS values were as follows: 8.5 ± 1.2 for Group A, 14.3 ± 2.1 for Group B, 10.8 ± 1.5 for Group C, and 6.9 ± 0.9 for Group D. The SBS was substantially higher in Group B as contrasted with the other groups (p